Assessing the Suitability of the Vermpirai Water Supply Wells in Thenmaradchi Aquifer in Jaffna Peninsula, Sri Lanka by Analyzing Seasonal Water Quality and Geochemical Parameters. - Saravanan, S.; De Silva, C.S.; Mikunthan, T. (Open University of Sri Lanka (JET OUSL), 2023)
Access to safe drinking water is a fundamental human right, and an essential step towards improving living standards. The National Water Supply and Drainage Board, Jaffna is supplying drinking water to around 20,000 people. However seasonal variation of groundwater quality of intake wells is a serious concern. These intake wells are comparably used for extracting more water and they are in active operation during the whole year in the identified aquifers. The main objective of the study is to assess the suitability of the Vermpirai water supply Intake wells in the Thenmaradchi aquifer by analyzing seasonal water quality and geochemical parameters with 2018 data. Water quality data of intake wells from 2013 to 2017 were obtained and the seasonal and periodical variation of quality parameters were analyzed. Seasonal water quality analyses were carried out for wet (April) and dry (August) seasons in 2018 in the intake wells and control wells from the same aquifer to see the variation of geochemical characteristics of the aquifer. All the wells are located in the sodium-calcium chloride sulphate type water, except control well no 03, which showed the mixed type water in both seasons and others were changed to sodium chloride type water in the dry season. The chloride ion concentration of the intake wells was increased prominently in the dry season, it may be due to the continuous extraction. High chloride contamination may be due to the influence of saltwater lagoons. The specific area in the Thenmaradchi Aquifer has sodium chloride type low-quality water, chloride ion, and total hardness were in high concentration and showing high seasonal fluctuation. Geochemical parameters were showing chloride ion influences other than the geological influences; this has shown that the aquifer is vulnerable to saltwater contamination. Hence, the Vermpirai scheme needs additional water sources or alternative water sources to meet the increasing demand and to protect the further deterioration due to continuous pumping.
Keywords: Aquifer; Intake well; Seasonal variation; Water quality